The Effect Of Company Growth, Company Profitability, And Market Capitalization On Firm Value Through Environmental, Social & Governance (E.S.G.) In Energy Sector Companies On The Indonesia Stock Exchange (Idx) For The Period 2017 – 2023 - Elwin, Beni; Nurwulandari, Andini (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research aimed to determine the influence of Company Growth, Company Profitability, and Market Capitalization through Environmental, Social, & Governance on Company Value. This study uses a quantitative approach with data from financial statements published and audited by independent institutions. It also uses the SmartPLS 3.2.9 application in the research data processing process. The Population of this study is 87 issuers in the energy sector. Through several stages, as many as ten issuers were obtained as research samples with seven years of observation. The study results show that Profitability and Market Capitalization have a positive and significant effect on Environmental and Social Governance (E.S.G.), and Profitability and Market Capitalization have a positive and significant impact on Company Value. Meanwhile, the Corporate Growth variable has a negative and insignificant impact on Environmental, Social, and governance (E.S.G.). Corporate Growth and Environmental, Social, and governance have an adverse andnegligible effect on Company Value. Environmental, Social, and governance (E.S.G.) cannot mediate the influence of Company Growth, Profitability, and Market Capitalization on Company Value. The Total Determination Coefficient in this study was 0.335 or 33.5%. That is, the information contained in the data is 33.5%, which the model can explain. At the same time, the rest is explained by other variables not included in the model.